Integration of bubble phobicity, gas sensing and friction alleviation into a versatile MoS2/SnO2/CNF heterostructure by an impressive, simple and effective method. Issue 36 (10th September 2020) - Yang, Fuchao; Wang, Caiyun; Guo, Zhiguang
Abstract : The design strategy is to anchor MoS2 /SnO2 beads onto one-dimensional CNFs for bubble phobicity, gas sensing and friction alleviation. Abstract : The engineering of composite surfaces and interfaces of materials at the micro/nano-hierarchical level with multiple functionalities is attracting increasing attention due to their biomimetic technological applications, especially the self-cleaning with gas bubbles, gas sensing and sustainable anti-friction performances. Herein, the ternary MoS2 /SnO2 /CNF (CNF: carbon nanofiber) was designed and assembled by an in situ facile method. Interestingly, its microstructure exhibits a necklace-like morphology. The MoS2 /SnO2 /CNF shows desirable bubble phobicity under water and in a PAO4 environment on various substrates, an acceptable gas-sensing ability to target gas with a detection limit of 5 ppm and fascinating tribological performances for additives in different kinds of base/lubricating oils. These results demonstrate that the necklace-like ternary MoS2 /SnO2 /CNF structure could have numerous applications in one system and may provide a new perspective in composite surface and interface materials engineering.